211k views
1 vote
Solve for the specified variable

Solve for the specified variable-example-1

1 Answer

3 votes

Answer:


s = (2A)/(f) - z

Explanation:

Given:


A = (1)/(2)f(s + z)

Required:

Make s the subject of the formula

SOLUTION:


A = (1)/(2)f(s + z) (given)

Multiply both sides by 2


2*A = (1)/(2)f(s + z)*2 (multiplication property of equality)


2A = f(s + z)

Divide both sides by f


(2A)/(f) = (f(s + z))/(f) (division property of equality)


(2A)/(f) = s + z

Subtract z from both sides


(2A)/(f) - z = s + z - z (Subtraction property of equality)


(2A)/(f) - z = s

Rewrite the equation


s = (2A)/(f) - z

User Zigdawgydawg
by
6.0k points